2018
DOI: 10.1097/ipc.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus–Associated Guillain-Barré Syndrome in a Returning US Traveler

Abstract: Zika virus (ZIKV) infection has been associated with Guillain-Barré Syndrome (GBS). Roughly 60% of people in countries such as the U.S. live in areas at risk for seasonal spread of ZIKV. ZIKV belongs to a class of diseases that is not typically seen in hospital settings across the U.S. and Europe. We describe the case presentation, management, and treatment of ZIKV infection complicated by GBS. A 64-year-old woman with recent travel to the Dominican Republic presented with rash followed by an acute, ascending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Traveller/non-traveller populations: In studies included in this update, we found additional evidence of GBS in both travellers and non-travellers with ZIKV infection. Ten publications report on 11 travellers 218, 220, 222224, 227, 229, 232– 234 , while 34 publications report GBS due to ZIKV in 402 non travellers 4, 44, 118, 219, 221, 225, 226, 228, 230, 231, 235– 237, 239– 247, 249, 251, 253260, 262, 263 .…”
Section: Resultsmentioning
confidence: 99%
“…Traveller/non-traveller populations: In studies included in this update, we found additional evidence of GBS in both travellers and non-travellers with ZIKV infection. Ten publications report on 11 travellers 218, 220, 222224, 227, 229, 232– 234 , while 34 publications report GBS due to ZIKV in 402 non travellers 4, 44, 118, 219, 221, 225, 226, 228, 230, 231, 235– 237, 239– 247, 249, 251, 253260, 262, 263 .…”
Section: Resultsmentioning
confidence: 99%
“…Whether infants and the elderly are at an increased risk for this complication is not known. The lack of cases with Guillain-Barré syndrome or intrauterine infections in our study probably reflects the small number (to date) of cases in Israel as both Guillain-Barré syndrome 21 and adverse pregnancy outcomes 22 have been described in travelers.…”
Section: Discussionmentioning
confidence: 57%
“…Mice immunized with PBS served as the control. The detection limits were~10 3 RNA copies/mL (sera),~5 × 10 2 RNA copies/g (eye, heart, and spleen), and 2.5 × 10 2 RNA copies/g (muscle and testis). Data are expressed as the mean ± s.e.m (n = 5).…”
Section: Discussionmentioning
confidence: 98%
“…Most ZIKV infections are asymptomatic or show mild clinical symptoms, such as fever, headache, or rash. However, some adults infected with ZIKV present with Guillain-Barré syndrome (GBS), a disorder of the nervous system that results in muscle weakness and/or paralysis [2,3]. In addition, infection during pregnancy may cause congenital Zika syndrome (CZS), which is associated Laboratory Animals, National Research Council Committee [28].…”
Section: Introductionmentioning
confidence: 99%